PEMAHAMAN TEKSTUALIS ORMAS ISLAM TERHADAP HADIS SUJUD TILAWAH - Ananda, Yassinta; Wendry, Novizal (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2023)
This article aims to analyze Muhammadiyah and Nahdhatul Ulama's understanding of the Hadith of prostration. The aspects examined are the sources of reference and how these two organizations interpret through their official websites. This research uses a qualitative method by referring to data uploaded on both websites. The author interpreted the data using a discourse analysis approach. The author's assumption is that all worship practices in Islamic mass organizations that exist today cannot be separated from the role of the Prophet SAW and the Companions in the application of practices in mass organizations in Indonesia. This article proves that both organizations recognize the existence of the Hadith of prostration. Based on the source of the hadith they issued the procedure and its virtues. From this understanding, it turns out that both Muhammadiyah and Nahdhatul Ulama understand it textually. This finding refutes the common assumption that Nahdhatul Ulama tends to be contextualist in understanding hadith.